Paraneoplastic sclerodermiform syndrome--case report. - Rovisco, J (2014)
Occasionally, auto-immune diseases may emerge as paraneoplastic syndromes. This is especially recognized in the case of polymyositis/dermatomyostis, but it is an extremely rare event in systemic sclerosis (SSc). The authors report the case of a sixty-year-old woman who presented with Raynaud's phenomenon and rapidly progressing skin thickness of the forearms, hands and lower limbs. Patient evaluation revealed a colorectal carcinoma. The patient was referred to the oncology department. This concomitance of cancer and SSc with rapid progression of the latter, suggests that the scleroderma might have a paraneoplastic origin. Such an hypothesis deserves consideration in every case as early diagnosis may be decisive to control the progression of either disease.